2014
DOI: 10.1246/cl.141085
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Activity of Silver Nanoplates on Human Promyelocytic Leukemia Cell Lines

Abstract: The physical and chemical properties of silver nanomaterials are highly dependent on their shape and size. Recently, Ag nanoparticles have been reported to be useful for medicinal and pharmaceutical applications including anticancer activity. In this study, we showed that Ag nanoplates possess significantly higher antiproliferative activity on human promyelocytic leukemia cells, HL-60, than spherical nanoparticles. The triangular Ag nanoplates induced apoptosis in the cells and were located in the same subcell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Silver nanostructures, including nanoplates, are renowned for their diverse applications [47]. The distinct optical properties of silver nanoplates, like surface plasmon resonance [3,41], along with their physiological attributes, including antibacterial and anticancer activities [11,48], are intricately tied to their size and shape. Consequently, our research offers promising avenues for developing a range of functional silver nanostructures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver nanostructures, including nanoplates, are renowned for their diverse applications [47]. The distinct optical properties of silver nanoplates, like surface plasmon resonance [3,41], along with their physiological attributes, including antibacterial and anticancer activities [11,48], are intricately tied to their size and shape. Consequently, our research offers promising avenues for developing a range of functional silver nanostructures.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to control the shape and size of inorganic nanostructures is critical for material science and nanotechnology, since these properties have substantial impacts on the functional attributes of the synthesized materials [1][2][3][4]. It has been shown that material morphology influences a wide array of the functional properties of nanostructures, including optical, electrical, catalytic, and biological, among others [5][6][7][8][9][10][11]. The use of biomolecules, such as biomineralization peptides, for the synthesis of inorganic nanostructures has gained popularity due to their inherent capacity to self-assemble, combined with their ability to chelate a wide variety of different metal ions [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Cell cycle analysis was performed as described previously [ 13 ]. Briefly, 1 × 10 6 HL-60 cells were seeded on a 10-cm tissue culture dish with 10 ml of medium and incubated for 24 h before TAP-4PH treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the shape of the nanoparticles also affects their toxicity to tumor cells. Sakaguchi et al showed that the shape of Ag nanomaterials plays an important role in its anti-proliferative activity, and the activity of antiproliferative silver nanomaterials highly depends on its nanostructure [115]. The Ag nanoplates have significantly higher anti-proliferative activity against human promyelocytic leukemia HL-60 cells than spherical nanoparticles.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%